Matelea ojadapantha (Apocynaceae; Asclepiadoideae; Gonolobeae; Gonolobinae), a new species from México - Alvarado-Cárdenas, Leonardo Osvaldo; Islas-Hernández, Carla Sofia; Chávez-Hernández, María Guadalupe (Phytotaxa, 2020)
A new species of Matelea from central and southern México with green to black corollas and pubescent lobes is described here: Matelea ojadapantha. This taxon is morphologically similar to M. schaffneri and M. atrostellata but differs by the corolla and corona morphology and has a disjunct geographic distribution. Descriptions, illustrations, morphological comparisons, map of the distributions of this species as well as their conservation status is provided. This discovery highlights México as a center of diversity of the genus, as more than 70 species are currently known in the country. Furthermore, 60% of those species are endemic.